Gestão territorial: o georreferenciamento como ferramenta de acesso, garantia e regularização de territórios historicamente reconhecidos - SIQUEIRA, Heloisa Márcia dos Reis (2022)
The different social movements, in addition to fighting for the adoption of affirmative policies in favor of black people, have always pleaded for the adoption of a land policy based on the principles of respect for their sociocultural and ethnic diversity. Despite the great advances registered, many difficulties persist in the effective control and social participation of quilombola organizations in the elaboration, follow-up and monitoring of public policies for their communities. The present work seeks to demonstrate the georeferencing activities carried out in the Quilombola do Abacatal Community, located in the Municipality of Ananindeua, state of Pará, through the partnership between the Federal University of Pará (UFPA) and the Instituto de Terras do Pará (ITERPA), using research tools. geoprocessing, allowing better precision and contributing significantly to the process of regularization, recognition, delimitation and titling of legally protected territories.